2022
DOI: 10.3390/metabo13010005
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Metabolomics of Insulin Intoxications and the Potential Application to Find Hypoglycemia-Related Deaths

Abstract: Postmortem metabolomics can assist death investigations by characterizing metabolic fingerprints differentiating causes of death. Hypoglycemia-related deaths, including insulin intoxications, are difficult to identify and, thus, presumably underdiagnosed. This investigation aims to differentiate insulin intoxication deaths by metabolomics, and identify a metabolic fingerprint to screen for unknown hypoglycemia-related deaths. Ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…In addition, postmortem metabolomics in a screening test was able to identify potentially hypoglycemia-related deaths in a large randomly selected cohort. 16 The current study also supports the hypothesis that postmortem metabolomics can effectively discriminate CoD. Herein, using the independent test set of over 1,000 cases, the specificity-optimized model resulted in an average sensitivity of 45% and specificity of 96% for the five CoD groups.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In addition, postmortem metabolomics in a screening test was able to identify potentially hypoglycemia-related deaths in a large randomly selected cohort. 16 The current study also supports the hypothesis that postmortem metabolomics can effectively discriminate CoD. Herein, using the independent test set of over 1,000 cases, the specificity-optimized model resulted in an average sensitivity of 45% and specificity of 96% for the five CoD groups.…”
Section: Discussionsupporting
confidence: 83%
“… 19 In the previous oxycodone and insulin intoxication studies, 21 and 12 acylcarnitines, respectively, were observed at lower abundances in intoxication cases compared to controls. 15 , 16 In the current study, acylcarnitines C14, C18:1-OH, and C18:2 were also identified, with the drug intoxication group showing the lowest relative abundance of these, as well as four other acylcarnitines, compared to the other CoD groups. Although the current study identified fewer acylcarnitines that discriminate the drug intoxication groups from the other CoD groups compared to previous studies, this could be attributable to the high degree of heterogeneity within this group.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations